(untitled) (Global Journal of Management and Business Research, 2011)
This study tests the market efficiency of the Japanese equity market. The analyses compare the performance of a portfolio consisting of exchange-traded funds (ETFs) with that of the overall market, exemplified by the Topix Index, during the period of June 30, 2008 to June 30, 2009. The ETF portfolio is constructed according to the Modern Portfolio Theory (MPT) developed by Harry Markowitz in 1952. The study concludes that an optimal ETF portfolio can outperform an overall market index when performance is measured using the Sharpe ratio, i.e., the return per unit of risk.